Before Boas: the genesis of ethnography and ethnology in the German Enlightenment - Vermeulen, Han F. (Critical studies in the history of anthropology, 2015)
"An extensive study of the emergence of ethnology and ethnography, and how theories in Europe and Russia during the eighteenth century experienced a paradigm shift with the work of Franz Boas starting in 1886"--